IMPLEMENTATION OF AN INTEGRATED POLLUTION CONTROL STRATEGY: A CASE STUDY OF MUNCAR FISH PROCESSING AREA - Muhammad Romli dan Suprihatin (Jurnal Teknologi Industri Pertanian, 2008)
ABSTRACTMuncar is one of a few major fish processing complex, which contributes significantly to the local as well as national economic development since most of the products is export oriented.  Majority of industry is characterized by the use of a relatively old type of machinery and facility and of improper waste control and management.  The fish processing as well as its related economic activity has now caused a serious environmental problem especially nuisance and water/coastal pollution.  The important environmental aspects identified include high process water consumption, less efficient use of energy and materials, and minimum implementation of industrial waste control and management.  In order to contribute to the government in establishing the framework of environmental management program in the area and in particular to assist the industry in improving its production and environmental performance, an integrated industrial pollution control strategy is proposed.  The strategy consists of input as well as output pollution control measures based on a comprehensive and reliable data of existing environmental performance.  The ultimate goal is to sustain and balance the environmental functions, namely economical, social and ecological functions.  The overall strategy exhibits a multi-year program implementation and involving many relevant government institutions and industries.  This paper describes the proposed strategy, which is now adopted by the government as a pollution control program of Muncar for the year 2007-2012.  At this present stage, the work focuses on potential implementation of input pollution control measures using cleaner production approach, such as waste prevention, reduction, reuse and recycle and their benefits to industry and environment.Keywords: cleaner production, fish processing, pollution control program, waste control and management.